The dry matter digestibility characteristics of tropical tree legumes using menke in vitro gas production technique - Dicky Pamungkas; Cesar C Sevilla (Jurnal Ilmu Ternak dan Veteriner, 2003)
The amount of gas released when a feed was incubated in vitro with rumen fluid, was closely related to the digestibility of the feed. The experiment using Menke in vitro gas production was conducted to determine the dry matter digestibility of tropical tree legumes; Leucaena leucocephala, Flemingia macrophyla, and Gliricida sepium. The samples were collected from Institute of Animal Science farms of the University of the Philippines at Los Banos. The amount of gas produced were recorded at 3, 6, 12, 48 and 72 hours of incubation. To estimate the volume of gas, the equation of Tuah was adopted; while to describe the course of gas production, the equation of MCDONALD was used. The washing loss was not measured and assumed to be zero. Results showed that leucaena at 12 hours was the highest in the volume of gas produced (1.217 ml/g DM). There was a similarity of highly increase of the gas produced between gliricidia and flemingia at 24 hours of incubation i.e 1.60 ml/g DM and 1.60ml/g DM. The potential extent gas production at 72 hours (b value) and the gas production rate (c value) of three legumes were no significantly different. According to the logarithmic-curve of gas volume produced, leucaena tended to be the highest of increase in potential extent and the gas production rate. The different rate of gas production in related to incubation reflected the dry matter digestibility of the three legumes in the rumen.   Key words: In vitro gas production, dry matter digestibility